PMO-143 The use of dry blood spot testing (DBS) for viral hepatitis in mosques-a pilot study of 3 surrey centres. (28th May 2012) - Readhead, S; Ahmed, A; Jenkins, H; Nicholls, M; Berry, P; Foster, G; Ala, A
Abstract : Introduction: Chronic Viral Hepatitis (CVH) affects ˜0.5% of native UK population. However, endemicity varies world wide & previous studies show that ethnic minorities are likely to preserve the higher rates of their region of origin. The estimated prevalence of chronic HBV & HCV in Pakistan is >5% & the current UK Pakistani population is >1.2 million. The study aimed to (1) characterise HBV & HCV prevalence in a local Pakistani community within Surrey using DBS testing (2) test the hypothesis that 2nd generation immigrants (ie, those born in UK) retain this higher prevalence (3) promote awareness of viral hepatitis within this population. Methods: We approached community leaders of three Woking (Surrey, UK) mosques & prospectively arranged testing sessions over 10 months (2011–2012), which were advertised during religious gatherings. Following approval by the Local Ethical Board & formal consent, finger prick DBS were tested for HBsAg, HBcore antibody, antiHCV Ab, HCV (Genotype & RNA quantification). Volunteers filled out a questionnaire outlining risk factors for CVH. Subjects who were HBsAg and/or AntiHCV Ab were invited back to the Mosques for focused counselling & offered outpatient confirmatory testing including specialist Hepatology assessment & treatment as necessary. Results: A total of 219 subjects were tested (164M, 55F), age 18–81 yrs, mean age 45 yrs, median 44 yrs & modal age range 30–39 yrs. The mean total duration of stay in the UK prior to testing was 24 yrs; 195 cases (89%) were of Pakistani origin of which there were 176 1st & 19 2nd gen immigrants. Of those tested, 4(2F & 2M) were HBSAg+ve and four (all M) were antiHCV+ve with 3HCV RNA+ve (2Genotype 3a and 1, 3k). Definite risk factors for CVH transmission were not identified. Mean duration of stay in the UK for +ve cases was 13 yrs, all were 1st generation Pakistani (fibroscan score <8 kPa, normal LFTS, two with prior family history and three were first degree relatives). Conclusion: DBS testing confirms that our local Pakistani community has retained CVH prevalence rates atleast seven times greater than that of the native UK population. Primary & secondary physicians need better awareness to engage & identify individuals in susceptible ethnic populations. This study has not picked up any cases of viral hepatitis in 2nd generation immigrants & further work is required to conclusively analyse this subset of the community. Our results suggest inequalities in health related to viral hepatitis in the Pakistani population & provide evidence for a wider UK study in this vulnerable group. Places of worship may act as focal testing points to improve screening uptake, management & potential treatment of viral hepatitis in at risk populations. Competing interests: None declared.